South America, east and south coasts, Estrecho de Magallanes to Cabo de Hornos / prepared and published by the Defense Mapping Agency Hydrographic/Topographic Center (United States. Defense Mapping Agency. Hydrographic/Topographic Center, 1994)
28th ed., June 18, 1994 (Correct through NM 25/94) Depths shown by soundings and isolines.; Relief shown by spot heights.; "From Argentine and Chilean charts to 1978."; "Copyright 1994 by the United States Government. No copyright claimed under Title 17 U.S.C."; Includes index to next larger scale charts and compilation diagram.; "Soundings in meters." Color; 1:566,820